Identification of variants in SWI/SNF complex genes associated with neurodevelopmental disorders - Liang, Chen; Shi, Haihong; Chen, Yanjuan; Wang, Xia; Jin, Jieyuan; Su, Liqun; Tang, Lijun; Li, Huihong; Ling, Fei; Li, Haoxian; Zhang, Yanghui (Frontiers in Genetics, 2025)
IntroductionNeurodevelopmental disorder (NDDs) such as intellectual disability, developmental delay encompasses a diverse group of conditions caused by the disruptions in the central nervous system (CNS) during development. Variants in the SWItch/Sucrose non-fermentable (SWI/SNF) complex genes are significant contributors to NDDs. ARID2, ARID1B, and SMARCC2 are important subunits of the SWI/SNF complex, and their variants can also result in Coffin-Siris syndrome (CSS), a type of NDDs characterized by CNS disorders, global developmental delay, visual/hearing impairment, distinct facial features, and congenital heart disease (CHD).MethodsThree NDDs families were recruited, and whole-exome sequencing and Sanger sequencing were used to detected their causative variant.ResultsWe described their symptoms and identified three variants of SWI/SNF complex genes unreported in disease cohorts, including a deletion variant of ARID2 (NM_152641: c.2901delC, p.Asn967LysfsX2), an insertion variant of ARID1B (NM_001374828: c.6532_6533insT, p.Trp2178LeufsX34), and a missense variant of SMARCC2 (NM_003075: c.2920C>G, p.Pro974Ala). Additionally, we compiled known variants in ARID2, ARID1B, and SMARCC2 associated with CSS/NDDs.ConclusionWe reported three SWI/SNF variants in three NDDs families. Our identification broadened the variant spectrum of SWI/SNF genes and contributed to the genetic counseling and molecular diagnosis of NDDs.